Analysis of the Influence of Sharia Pension Fund Investments and Participation on the Human Development Index and Economic Growth in Indonesia - Laily Nisa, Fauzatul (Journal of Economics Development Issues, 2025)
This study aims to analyze the impact of sharia pension fund investments and participation on the Human Development Index (HDI) and economic growth in Indonesia. The research employs a quantitative method with a multiple linear regression approach to examine the relationship between the independent variables—total investment in sharia pension funds and the number of participants—and the dependent variables, namely HDI and GDP per capita growth. Secondary data from 2014–2022 were utilized, sourced from the Financial Services Authority (OJK), Central Statistics Agency (BPS), and annual reports of Islamic financial institutions. The results show that sharia pension fund investments significantly influence HDI and economic growth, while participation also contributes positively, albeit to a lesser extent. This study emphasizes the importance of managing sharia pension funds in compliance with sharia principles to support sustainable economic development.